Peran Tasawuf Kebangsaan dalam Menumbuhkan Nasionalisme dan Harmoni Sosial (Telaah Atas Pemikiran Tasawuf Kebangsaan KH. Achmad Shiddiq dan Habib Luthfi bin Yahya) - Muvid, Muhamad Basyrul; Wahyudi, Mukhammad; Bagus Kurnia PS, Alaika M. (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The dichotomy between national identity and religious values often appears to operate separately. However, the integration of spirituality into national life is crucial for sustaining peace, unity, and prosperity. This study examines how the concepts of tasawuf kebangsaan (national Sufism) as advocated by Kyai Achmad Siddiq and Habib Lutfi bin Yahya contribute to developing patriotism through educational paradigms in the face of rapid modernization. Using a qualitative methodology with a literature-based approach, this research explores books, journals, and primary sources authored by both figures. The data analysis employs interpretative and comparative techniques to distill their philosophies into actionable models for cultivating nationalism through religious principles. The findings reveal that the national Sufism introduced by these scholars promotes tolerance, social harmony, and collective unity. Their teachings highlight the importance of balancing spiritual devotion with social responsibility, emphasizing love for one's country as an expression of faith. This approach integrates humanistic Sufi principles into education, guiding society to respect diversity while working together toward national progress. The study concludes that this model offers a viable framework for modern civic education, countering materialism and individualism through ethical and spiritual enrichment